Correlation between Criteria Air Pollutants and Daily Case of COVID-19 Pandemic in Padang City - Sari, Putri Nilam (Program Pascasarjana Universitas Sriwijaya, 2023)
From the concept of the epidemiological triangle, air pollution is a risk factor that becomes a carrier of disease agents and affects the vulnerability of the human body, including COVID-19. This study aims to see the correlation between PM10, CO, O3, SO2, and NO2 with daily cases of COVID-19 in Padang City. This study uses an ecological study using one year data (March 26, 2020 - March 26, 2021). Data for specific pollutants were obtained from reanalysis datasets of the European Center for Medium-Range Weather Forecast (ECMWF). Meanwhile, data on the COVID-19 pandemic was obtained from the daily report of the Padang City. Spearman and Pearson correlation tests were used to assess the correlation of specific pollutants with COVID-19 daily cases. The results found that CO, O3, SO2, and NO2 correlated negatively with COVID-19 daily cases at lag 0, lag –7, lag –14, and lag –21. In contrast, PM10 positively correlates at lag 0 and lag -7. Social distancing also had a significant relationship with the concentrations of O3 and PM10. Understanding the contribution of air pollutants to the increase of COVID-19 daily cases is essential for preventing more serious health impacts and requiring policy to control the emissions.